Revolutionizing Freud: Marcuse on the Psychology of Domination, Resistance, and Emancipation - Ocay, Jeffry V. (Silliman Journal, 2022)
Following Marx, Herbert Marcuse believes that the internal logic of overproduction and excessive consumption, combined with massive pauperization will lead to the self-destruction of capitalist society. But the political events of mid-20th century made Marcuse realize that Marx’s notion of the necessary transition from capitalism to socialism did not happen. What happened instead were the integration of the proletariat into the status quo, the stabilization of capitalism, the bureaucratization of socialism, and the absence of a revolutionary agent for progressive social change. For this reason, Marcuse appropriated Freud’s theory of instincts in order to provide Marxism an anthropological basis. I argue that Freud’s theory of instincts provided Marcuse with a model for a psychology of domination and resistance, and a model to think anew the philosophical conditions of emancipation: the agent of social transformation is the biological individual. I argue further that Marcuse’s appropriation of Freud’s theory of instincts is aimed to explain why the transition from capitalism to socialism did not happen, why, especially in the 1930s, the revolutionary class had been dissolved and became conformist, and how this conformism was even extended into the postwar era.